Scallop ice shape characteristics of swept wing based on large-scale icing wind tunnel experiment - WANG, Qiang; CHEN, Ningli; WANG, Yuanbo; LI, Weihao; LIU, Yu; YI, Xian (Chinese journal of aeronautics, 2023)
Scallop ice is a special phenomenon that occurs during swept wing aircraft passing through icing clouds. It poses a great challenge for the icing safety assessment that the complex scallop ice shape feature and its mechanism are still unclear. In this work, a large-scale icing wind tunnel experiment of swept wing designed by NACA0012 airfoil is conducted in the Icing Wind Tunnel of China Aerodynamics Research and Development Center. The detailed three-dimensional ice shapes under 0°, 15°, 30° and 45° swept angles are obtained by laser scanning technology. The experimental results show that with the swept angle increasing from 0° to 45°, the 2D double ice horn structures show certain spanwise variation, and finally transform into complete scallop ice with ice thickness greatly enhanced in the stagnation line region. The empirical mode decomposition of the spanwise ice curve captures the high-frequency fluctuation on the scallop ice caused by the small-scale roughness element, while the trend with low frequency is not obvious. Based on the experimental data, a new complete scallop ice geometric model, named 5Points-5Lines-2Arcs (5P-5L-2A) model, is proposed, which can provide important basis for the quantitative description of complex scallop ice shape.